Decision tools for pest management - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Decision tools for pest management edited by G A Norton and J D Mumford 1993 288pp ISBN 0 85198 783 4 Hbk price UKL37.50 CAB International, Wallingford Oxon OX10 ODE. UK